Piecing me together - Watson, Renée (Bloombury, 2017)
Tired of being singled out at her mostly-white private school as someone who needs support, high school junior Jade would rather participate in the school's amazing Study Abroad program than join Women to Women, a mentorship program for at-risk girls.